Analisis Hukum Solat Rebo Wekasan Dalam Kitab Tarjumān Karangan KH. Abdul Hamid: Analysis of the Rebo Wekasan Prayer Legal in the Tarjumān Book by KH. Abdul Hamid - Imamuddin,; Ali, Abdul Karim (Online Journal of Research in Islamic Studies, 2022)
This study will discuss the view of KH. Abdul Hamid on the Rebo Wekasan prayer in the Tarjumān book (1800-1900 BC). The Tarjumān book is essentially the kitab of tawhid (oneness of God) and fiqh (Islamic jurisprudence). However, its extensively discuss the subject of fiqh. To name a few such taharah (abolition), prayer, fasting, inheritance, pilgrimage, marriage and the general discourse. Rebo Wekasan prayer is a prayer performed on the last Wednesday of the month of Safar with the aim of being safe from the calamities that descend on that day for one year. Many people practice the Rebo Wekasan prayer whether from student, scholar, sheikh to the general public. The objective of this study is to identify the view of KH. Abdul Hamid on the Rebo Wekasan prayer. To meet this objective, the researcher uses a qualitative method of library research. The study finds that the practice of this prayer is based on the kasyaf (heart view) of the Sufis which is associated with some hadith that cannot be used as an argument for a problematic cause up to the level of mawḍū‘ (false).